Exploring the relationship between landscape characteristics and urban vibrancy: A case study using morphology and review data. (December 2019) - Meng, Yuan; Xing, Hanfa
Abstract: Urban vibrancy is a vital component that supports urban form and is dependent on the physical entities in urban landscapes. Thus, the relationship between urban landscapes and urban vibrancy is a major concern for city planners. While existing studies mainly capture mixed land use, density, and accessibility properties of the physical environment, urban characteristics depicted by the city morphologies have seldom been addressed. To fill this gap, a novel framework is proposed in this paper to explore the relationship between landscape characteristics and urban vibrancy. First, research approaches for delineating multi-level urban landscape characteristics – including places, land use, and single and multiple landscape elements – using spatial metrics were analysed. Then, place-based reviews from social media data were applied as proxies to quantitatively measure urban vibrancy. Finally, regression analyses were proposed to assess the relationship between landscape characteristics and urban vibrancy. Satisfactory regression model performances were attained with adjusted R 2 values of 0.65, 0.65, 0.66, and 0.67 at each landscape characteristic level. The results indicate that changes in urban vibrancy are variable and highly dependent on the proposed multi-level characteristics. These findings may provide guidance for city planning and urban landscape design. Highlights: Approaches to explore the relationship between landscape characteristics and urban vibrancy are proposed. Multi-level landscape characteristics are delineated using spatial metrics. Methods for selecting spatial metrics that effectively represent landscape characteristics are designed. Place-based reviews from social media data are utilised to quantify urban vibrancy.